Playing with the cultural pilgrimage to stimulate tourism: the xFORMAL project on cultural heritage and informal learning. [version 2; peer review: 1 approved, 2 approved with reservations] - Simona Marchesini; Annalisa Di Nuzzo; Anna Siri (Open Research Europe, 2024)
The focus on culture as an engine of sustainable development has favoured its gradual acquisition by institutions engaged in the protection and promotion of heritage as an enabling and systemic factor capable of connecting innovation, continue education, research, and citizen engagement in a single chain. Knowledge of the landscape that combines works of nature and humankind and its bio-cultural diversity makes it possible to identify innovative informal education and new tourist itineraries where the real experience is presented as a cultural pilgrimage. The European project of the Marie Skłodowska-Curie Programme RISE ‘Informal and non-Formal E-Learning for Cultural Heritage - xFORMAL’, currently halfway through its lifecycle, was born to create an informal way of accessing the cultural heritage of one's territory, revealing its past, history, and the civilisations that preceded us. After two years of closure due to the pandemic, this project reintroduced an authentic experience through gamification, a contact with landscapes, museums, and archaeological sites with physical, social, and cultural dimensions of their environments across space and over time. Building upon this foundation, the article delves into the intricate design and architectural principles that underpin the creation of the xFORMAL game, showcasing it as a paradigm of informal learning. This exploration includes a detailed analysis of the game's innovative design elements, educational strategies, and its role in facilitating an engaging and immersive learning experience outside traditional educational settings.